How does academic self-concept contribute to English language achievement in Chinese EFL college classes? - Zhou, Xiao; Kaur, Sidhu Gurnam (Frontiers in Psychology, 2026)
IntroductionThis study investigates how academic self-concept contributes to English language achievement among Chinese EFL college students, focusing on the mediating role of academic buoyancy and the moderating role of personal best. Guided by positive psychology theory, we clarify how self-belief, resilience, and self-referenced goal striving jointly shape English learning outcomes.MethodsData were collected from 364 undergraduates enrolled in a private university in southern China. Participants completed a structured questionnaire. Partial Least Squares Structural Equation Modeling was employed to examine the measurement and structural models, assess mediation and moderation effects, and evaluate model fit and predictive validity.ResultsThe measurement model showed satisfactory reliability and validity; the structural model tested direct, mediating, and moderating effects. Results indicated that academic self-concept positively predicted both academic buoyancy and English language achievement. Academic buoyancy also positively predicted English language achievement, yielding a significant partial mediation from academic self-concept to English language achievement via academic buoyancy. Moderation analyses revealed a non-significant personal best effect on the academic self-concept to personal best path, but a significant negative moderation on the academic buoyancy to English language achievement path, suggesting that the achievement benefits of buoyancy are weaker when students’ personal best orientation is higher.DiscussionThe findings highlight the pivotal roles of academic self-concept and academic buoyancy in enhancing English language achievement while revealing boundary conditions linked to personal best. Pedagogically, strengthening students’ self-belief and everyday academic resilience remains crucial; however, instructors should calibrate self-referenced goal setting to avoid inadvertently attenuating the performance yield of buoyant coping.